Impact of preoperative hemodynamic optimization on right ventricular failure after left ventricular assist device implantation. (3rd October 2022) - Briasoulis, A; Alvarez, P; Panos, A; Ruiz Duque, E
Abstract: Background: Preoperative hemodynamic parameters are linked to higher rates of right ventricular failure (RVF) after left ventricular assist device (LVAD) implantation. It is unclear if preoperative hemodynamic optimization decreases the incidence of RVF after LVAD. Methods: Single-center retrospective analysis of consecutive LVAD recipients between 2015 and 2020. Pre-operative right heart catheterization and a strategy of hemodynamic optimization were performed in all patients. Pre-operative right ventricular dysfunction (RVD) was defined by a CVP ≥16 mmHg and pulmonary artery pulsatility index (PAPi) <1.85. The optimization goal was defined as CVP <16 mmHg, PAPi ≥1.85, and Cardiac Index of ≥2.0. The main outcome was RVF (inotropes >14 days, discharge on home inotropes, or right ventricular mechanical support device). Results: 128 LVAD recipients (age 58 years, 74% male, 68% had non-ischemic cardiomyopathy, 45% were on home inotropes, HeartMate 2 in 61%, HeartMate 3 in 31%, and HVAD in 9%) were analyzed. Pre-operative RV dysfunction was present in 48% and these patients were younger, with higher rates of home inotropes, and intra-aortic balloon pump (IABP) pre-LVAD. Postoperative RVF occurred in 60% of patients with RV dysfunction and 40% of the patients without pre-operative RV dysfunction (p<0.002). 40% of patients with RV dysfunction achieved RV optimization goals (32% required IABP). Among those, 53% developed RVF-Post LVAD. RVF was numerically but not significantly higher among those with RV dysfunction who achieved hemodynamic goals (66% vs. 34%, p=0.37) vs. those that did not. Patients with RVF-post LVAD had 10% (n=5) in-hospital mortality. Conclusion: Pre-LVAD RV dysfunction based on hemodynamic markers is associated with RVF after LVAD implantation. In patients with RV dysfunction, a strategy of pre-LVAD "optimization" to achieve RV hemodynamic optimization goals did not affect the incidence of post-operative RVF. Funding Acknowledgement: Type of funding sources: None.